On-Line Microwave Moisture Technique Performance of Ferronickel - Indra, Win Adiyansyah; Azahar, Arman Hadi; Manap, Mustafa; Jamil Alsayaydeh, Jamil Abedalrahim; Irianto, Irianto (International Journal of Integrated Engineering, 2019)
The competency of observing continuous record of water content or moisture of minerals, then control it in actual real-time basis is crucial that will affects mineral ore quality, cohesivity, process control, material handling and flowability. This paper describes experiment of a Random Stratified Sampling Sweeping Microwave method, moisture content measurement technique that lessen interference, annulling or superimposing signal, that are normal deviations in moisture measurement using microwave transmission method. The technique is used for ferronickel ore running on a belt conveyor exit to the rotary dryer. It showed that high bed depth and high phase stability are essential requirements that must be achieved for successful microwave moisture measurement analysis of ferronickel ore. Attenuation parameter was the suitable parameter for the experiment, instead of Phase parameter, which is common parameter for the ferronickel application. The experimental results revealed  accuracy of 0.78wt%, standard error of 0.18 and regression of 0.73.